2023
DOI: 10.1039/d3ew00131h
|View full text |Cite
|
Sign up to set email alerts
|

Identifying and aggregating high-quality pathogen data: a new approach for potable reuse regulatory development

Abstract: To address decreasing water supplies, several US regulatory entities are developing regulations and guidance for the direct potable reuse (DPR) of wastewater, i.e., potable reuse with a limited or no...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…To expand the dataset to include other geographic locations and time periods, Darby et al identified other historical datasets meeting a minimum set of criteria and developed an approach to combine these highest-quality data into single pathogen distributions. 10 All data points from each of the selected studies were pooled together and log-transformed to produce a normally distributed dataset. The parameters of the resulting log-normal distribution were defined and values from the distribution were sampled for the estimation of LRT requirements.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…To expand the dataset to include other geographic locations and time periods, Darby et al identified other historical datasets meeting a minimum set of criteria and developed an approach to combine these highest-quality data into single pathogen distributions. 10 All data points from each of the selected studies were pooled together and log-transformed to produce a normally distributed dataset. The parameters of the resulting log-normal distribution were defined and values from the distribution were sampled for the estimation of LRT requirements.…”
Section: Resultsmentioning
confidence: 99%
“…This decision is relevant for regulatory development because it can impact the LRT required to protect public health. The following example shows how the Cryptosporidium LRT would be impacted by the use of 1) a conservative point 20 or 2) the aggregated, DPR-2 distribution 10 by keeping all other QMRA inputs equal (see Methods). The point estimate leads to a single LRT value of approximately 11 logs to achieve the daily risk goal of 2.7 × 10 −7 infections per person per day (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations